Nomadic Culture in Relation to Christian Faith - Wetapo, Welius; Samiun, Jothan; Yikwa, Komanius (Side: Scientific Development Journal, 2025)
The Baliem Valley is considered the center of civilization in the Papua Highlands. Its rich cultural diversity has made the Baliem Valley well known both nationally and internationally. Many traditional practices are still preserved to this day. One such tradition is the culture of Nomat. Prior to the arrival of the Gospel in the Baliem Valley, this practice was known as Wakun, but later the name was changed to Nomat. Nomat is a tradition of giving or repaying gratitude in anticipation of a person’s death. It is carried out by the family of the sick person as a form of payment or appreciation to the maternal uncles and aunts (the siblings of the patient’s mother) or to others who have contributed significantly to the patient’s life. Through the process of inculturation, Nomat can serve as a meaningful channel for the growth of Christian faith. Inculturation refers to the process by which the church embraces cultural practices as a medium for spreading the Gospel, without compromising the core purity of its message. The goal of inculturation in this context is to use Nomat as a platform for evangelism—both to the ailing individual and to the family and community members attending the Nomat event. Additionally, through a contextual pastoral approach, church leaders can educate congregants that the Nomat ceremony does not need to be extravagant or burdensome. Instead, the central focus should be the proclamation of the Gospel, thereby avoiding economic and social strain on families. The Mic Kelson Ai Hitigima congregation is one of the communities that continues to practice the Nomat tradition. Therefore, this journal aims to explore the inculturation of the Nomat tradition and its influence on the development of Christian faith within this church community. This research adopts a qualitative-descriptive approach, utilizing observation, interviews with church leaders, congregants, neighboring churches, and a literature review. The findings show that the Nomat tradition has a dual impact: it strengthens family bonds and fosters social responsibility as an expression of love and respect. However, if not approached wisely, it can also cause economic burden and social conflict within households. This paper employs a contextual pastoral approach to bridge the values of local culture with Christian teachings.